Increase Security of Image Encryption Depends on Change Pixel Location (Journal of the College of Basic Education, 2022)
In any communication, security is the most important issue in today’s world. The information security has be come one of the most signify can tproblemsin data communication. Lots of datasecurity and data hiding algorithmshavebeendevelopedinthelastdecade. Cryptography and steganography are the two major techniques for secret communication. In this paper, the secret text is first encryptedbyusingAESwhichhasverygood performanceandisamostpowerfultechnique. Now this encrypted text is embedded using steganography. Our proposed system gives threestages of security for secret. The main aim of proposed method to increase security of embedding and extraction phase using AESencryption,steganography and change pixel location. In order to evaluate performance the proposed algorithm performs series of tests. These tests include, PSNR and MSE.